Herpes zoster in a 4-year-old child with pulmonary tuberculosis: a case report - Nadya Nainggolan; Eric; Natasya Anditha Putri; Irene Dorthy Santoso (Science Midwifery, 2023)
Herpes zoster (HZ) is a dermatomal virus infection caused by the reactivation of latent varicella zoster virus (VZV) in sensory ganglia neurons that is previously exposed to primary varicella infection. Herpes zoster is a rare disease experienced in children and is often associated with an immunocompromised condition. A case of a girl four years old with a vesicle on the right chest which spread to the upper armpit and right inguinal was reported. The lessions were obtained on Thoracoaxilla as high as T4 and Inguinal as high as L1 dextra. The patient was treated with acyclovir doses of 30 mg/Kg/day for seven days and showed significant improvements.